Role of Common Contact Sensitizers in the Aetiopathogeneses of Prurigo Nodularis (Community Based Medical Journal, 2013)
Prurigo nodularis (PN) is a chronic condition characterized by itchy, papulonodular eruption of unknown etiology. It is a difficult condition to treat and often causes frustration to both the patient and the treating doctor. A variety of systemic conditions have been reported to be associated with Prurigo Nodularis including Allergic Contact Dermatitis. The present study evaluates the role of common contact sensitizers in the aetiopathogeneses of PN. DOI: http://dx.doi.org/10.3329/cbmj.v1i1.13822 Community Based Medical Journal Vol.1(1) 2012 11-13